Al-Islam wa al-Naṣrānīyah fī Indūnīsīyā - M. Amien Rais (Studia Islamika, 1995)
Since Indonesia declared its sovereignty and its independence in 1945, relations between Christians and Muslims in this country has been characterized by cooperation, tension and competition. Until the 1960s the number of Muslims about 90 percent of the entire population, but in the early 1990s this figure dropped to 87.5 percent. Two and a half percent of the 185 million people is about 4.5 million, and of course the number is not small. Tension and often coloring competition relations between the two religions up to now, and keep in mind that the future Indonesia will depend largely on the direction and prospects between Christianity and Islam.DOI: 10.15408/sdi.v2i1.842